AB0679 HEALTH ASSESSMENT IN FEMALE PATIENTS WITH SPONDYLOARTHRITIS: FOCUS ON REPRODUCTIVE SPHERE. (2nd June 2020) - De Martino, E.; Conigliaro, P.; Chimenti, M. S.; Triggianese, P.; Bosello, S. L.; Gremese, E.; Iannuccelli, C.; Spinelli, F. R.; Vadacca, M.; Perricone, R.
Abstract : Background: SpA patients experience a decreased quality of life due to social, emotional and relational life impairment in addition to pain, fatigue and joint damage. Sexual dysfunction (SD) is often neglected by both patients and clinicians, although articular and extra-articular manifestations of the disease can decrease the quality of sexual life. Previous findings showed that SD can affect from 27% to 67% of patients with rheumatic diseases. Data available on SD in rheumatic patients are poor and primarily focus on male ankylosing spondylitis patients Objectives: The aim of this study is to evaluate, in a group of female SpA patients, the presence of SD, its relationship with extra-articular manifestations and to estimate the correlation between disease activity and sexual activity. Methods: 52 SpA patients (including PsA, IBD-SpA and undifferentiated SpA-un-SpA) and 50 healthy controls (HC) were administered the Female Sexual Function Index (FSFI) questionnaire for the analysis of sexual function (score from 0 to 100). SD is defined by a score lower than 26. Disease activity was evaluated through DAPSA and BASDAI. SpA-HAQ and BASFI was also performed to assess functional status Results: There was a trend for a significantly greater proportion of SD in the patients (21%) than the controls (8%), χ 2 (1, N = 102) = 3.52, p = .06). Within the different groups, the percentage of those with SD according to the FSFI cut off were 23% of PsA patients, 25% of IBD-SpA patients, 11% of un-SpA patients, and 8% of healthy controls, however, when the patient groups were analysed separately these differences were not significant, χ 2 (3, N = 102) = 4.43, p = .22. Mean scores on the FSFI were lower for the total SpA patients group t(100) = 2.47, p = .02 compared to HC. When scores on the FSFI were analysed separately for each patient group, there was a trend for a significant difference between the groups, F (3, 98) = 2.43, p = .07, and follow up t-tests showed that only the PsA group scored significantly lower than the HC, t (100) = 2.56, p = .01 (see Fig. 1). Among the items of the questionnaire, questions regarding sexual desire, lubrication and discomfort were statistically significantly lower scores in patients compared to HC ( p = 0.001, p = 0.009, p = 0.02, respectively). For the overall patient group, the FSFI was significantly negatively correlated with the DAPSA ( r = -.37, p = .008), the SpA-HAQ ( r = -.30, p = .03) and the BASFI ( r = -.30, p = .03). Additionally, the PsA group showed a negative correlation between DAPSA scores and FSFI score ( r = -.38, p =.03) and the IBD-SpA group had a negative correlation between FSFI score and BASFI ( r = -.80, p = .002). Conclusion: Overall, the data generally show that SD is more common in SpA patients compared to HC and that SpA patients score lower on the FSFI. The negative correlations between the FSFI and scores on DAPSA, SpA-HAQ and BASFI suggest that sexual function may be poorer for patients with greater disease activity and poorer functional status. These findings could be due to the number of tender and/or swollen joints as well as chronic pain or fatigue patients often experience. A key limitation of this study is the small sample size. Future research will include a larger sample size. SD in patients with rheumatic disease is still a neglected field in clinical practice, however, its assessment could contribute to improved quality of life for patients Disclosure of Interests: erica de martino: None declared, Paola Conigliaro: None declared, Maria Sole Chimenti: None declared, Paola Triggianese: None declared, Silvia Laura Bosello Speakers bureau: Abbvie, Pfizer, Boehringer, Elisa Gremese Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Sanofi, UCB, Roche, Pfizer, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Sanofi, UCB, Roche, Pfizer, Cristina Iannuccelli: None declared, Francesca Romana Spinelli Grant/research support from: Pfizer, Speakers bureau: Lilly, BMS, Celgene, Marta Vadacca: None declared, Roberto Perricone: None declared